Assessment Rubric Design for Students’ English Problem-Solution Short Essay Writing - Widiastuti, Ni Made Ayu; Indriani, Ketut Santi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. This paper is aimed at describing the parts (paragraphing and contents) of problem-solution short essay necessary for the assessment and analyzing the approach used in designing the rubric. The data are taken from the sample of problem-solution short essay which belongs to the argumentative writing. The data were collected by using the documentation method and was analyzed qualitatively. The results show that there are two main parts in the analytical assessment rubric for the problem and solution short essay namely contents and grammar with the percentage values 60% and 40% respectively. The assessments of contents cover the suitable Title of the essay, Paragraphing, and Task response. Each of them has scoring scales. Meanwhile, grammar assessments that contains omission, addition, selection, ordering, plus the use of capital/small letters are measured by counting the numbers of errors. In order to get the total score of the essay, the excel sheets with certain formula are made. The top-down approach is appropriate in designing the analytical rubric for this type of short essay. It comprises of four steps, they are 1) choosing a framework for the intended assessment, 2) determining the criteria of the assessment, 3) adapting an existing rubric and designing the rubric for the specific learning purposes, and 4) use the rubric. The last step requires further observation and evaluation to test the effectiveness of the rubric that has been designed.Keywords: Assessment Rubric, Writing, Problem-Solution, Short Essay, Parts of Essay